Financial institutions, markets, and money - Kidwell, David S.; Blackwell, David W.; Whidbee, David A.; Sias, Richard W. (New Jersey John Wiley & sons, Inc., 2017)
Kidwell's Financial Institutions, 12th Edition presents a balanced introduction to the operation, mechanics, and structure of the U.S. financial system, emphasizing its institutions, markets, and financial instruments. The text discusses complex topics in a clear and concise fashion with an emphasis on "Real World" data, and people and event boxes, as well as personal finance examples to help retain topical interest.